An Easy Deprotection of Tosyl Esters with Superoxide Under Microwave Irradiation - S. Raghuvanshi, Raghvendra; P. Yadav, Virendra; K. Singh, Vinod (Current Microwave Chemistry, 2017)
Background: The p-toluenesulfonyl (tosyl) group is one of the most versatile protecting groups for phenols and alcohols, but its removal requires drastic conditions due to their high stability. Methods: In the course of reaction, (Et4N)O2 was generated in situ by the phase transfer reaction of KO2 and Et4NBr in dry DMF was subsequently allowed to react with tosyl esters, under microwave irradiation. Results: Tosyl esters were readily deprotected to their corresponding phenols and alcohols. Conclusion: In conclusion, a mild and efficient method for the removal of tosyl protecting group, using in situ generated tetraethylammonium superoxide under microwave irradiation, has been described.
Keywords: microwave irradiation